Analisis Nilai-Nilai Pendidikan Akidah Pada Serial Animasi Riko The Series Season 1 Episode 10 - Ade Alfina; Al Ikhlas (Prodi Pendidikan Keagamaan Islam, 2022)
Aqidah is the foundation that builds the Islam religion and as the basic for someone’s worship can be accepted so that aqidah becomes very important in the Muslim’s life. To instill a true and strong aqidah, namely tauhid, is through education that starts from childhood. Parents can give the aqidah education to their children by utilizing educational shows, one of them being animated series called Riko The Series on the YouTube platform. This research aims to analyze the aqidah education values contained in Riko The Series Season 1 Episode 10, entitled “Knowing the Isra Mi'raj Event”. The method used in this research is qualitative with content analysis and documentation techniques. The results showed that there are several aqidah education values contained in episode 10, namely 1) thayyibah sentences: astaghfirullah, greetings, Alhamdulillah, Subhanallah, Bismillah, Maasyaa Allah; 2) Asma’ul Husna: Al-Jamil, and 3) Faith in Allah’s Prophet: Isra Mi’raj’s Event.